Uticaj bazicnomotoricikh sposobnosti i antropometrijskih mera na specificnemotoricke vestine talentovanih vaterpolista - Aleksandrovic, M.; Naumovski, A.; Radovanovic, D.; Georgiev, G.; Popovski, D. (Facta Universitatis: Series Physical Education and Sport, 2007)
The purpose of this research is to determine the influence of basic motor abilities and anthropometric measures on the specific motor skills of water polo players in latent space. The subject sample consisted of a total of 89 water polo players aged 12 ± 6 who have been training water polo for at least 2 years and who partook in at least 1 federal tournament of the Water Polo Association of Serbia. The ascertainment of the morphological characteristics (14 tests), of the basic (12 tests) and specific (6 tests) motor skills level was performed by applying standardized tests. Factor analysis has been calculated to determine the space structure of the morphological, basic and specific characteristics of motor skills. A regression analysis was performed in order to determine the correlation between the influences of manifest basic motor skills as well as the morphological ones on the latent space of specific motor skills. A statistically relevant correlation between the whole predictor and the criterion has been confirmed.